Primary B-cell Lymphoma of the Thoracic Spine: a rare cause of Spinal Cord Compression - Zakaria@Mohamad, Zamzuri; Kow, Ren Yi; Chooi, Leng Low; Chooi, Asmah Hanim; Awang, Mohd Shukrimi (Cureus, Inc, 2021)
Primary non-Hodgkin lymphoma arising from the spine is exceedingly rare. Spinal cord compression can be the first presentation of a patient with primary spinal non-Hodgkin lymphoma. Due to its rarity and vague clinical presentation, the diagnosis can be confused with tuberculosis of the spine, a more common disease in this country. We present a case of primary thoracic spine B-cell lymphoma in a 45-year-old lady who presented with spinal cord compression. This case highlights the importance of obtaining histopathological samples for examination and the treating physician should be vigilant on this rare cause of spinal cord compression. Treatment can be initiated promptly once the diagnosis is established as primary spinal non-Hodgkin lymphoma carries a dire prognosis.